Vitamin D and exercise performance in female adolescent athletes - Riley Carro, S.; Kolb, R. D.; Volpe, S. L. (Current Sports Medicine Reports, 2025)
Vitamin D is both a required nutrient and a hormone and is necessary for growth and protein metabolism. Adolescence is a major period of growth and development, and thus, it is logical to consider how vitamin D may play a role in this stage of life. Our review specifically aims to examine the ways in which vitamin D intake affects female adolescent athletes. Although there is a paucity of data on the vitamin D status of adolescent female athletes, present data show that vitamin D status is below optimal concentrations in many athletes, especially in female athletes who primarily train indoors. Vitamin D supplementation may improve athletic performance and strength while decreasing risk of injury. More research is required to better evaluate vitamin D status in adolescent female athletes and to work on prevention of suboptimal vitamin D status through nutrition education. Furthermore, more research is required on the potential exercise performance benefits of optimal vitamin D in female adolescent athletes.